Maternal Serum Tumor Necrosis Factor Level in Women with Hyperemesis Gravidarum - Meran, Najmah M.; Hussein, Rifka M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Between 0.3% and 2% of pregnant women experience hyperemesis gravidarum. It is recognized by persistent and unexplained vomiting and dehydration, and the diagnosis is confirmed by significant loss of weight, usually more than 5% of the pre-pregnancy weight. Tumor necrosis factor-α is a multipotent cytokine that affects a vast array of cells. It is now well accepted that the tumor necrosis factor-α is crucial in the very early stages of pregnancy. Objectives: To assess the relationship between the tumor necrosis factor-α and hyperemesis gravidarum. Methods: This case-control study was carried out at the Baghdad Teaching Hospital, Obstetrics and Gynecology Department, from 1 January to 1 November 2022. The study involved 50 pregnant women, who suffered from hyperemesis gravidarum (mild or severe) as the case group, and another 50 healthy pregnant women as the control group, in the first trimester. The (Pregnancy-Unique Quantification of Emesis and Nausea) Index was used to evaluate the severity of the symptoms. Five milliliters of venous blood were taken to measure the tumor necrosis factor-α. Results: In contrast to the women in the control group, pregnant women with hyperemesis gravidarum had a mean hemoglobin that was significantly lower (10.8) g/dL compared to the control group (11.5) g/dL and their liver enzymes were significantly higher except for alkaline phosphatase, (294.4) IU/L compared to the control group (49.5) IU/L. Their mean tumor necrosis factor-α level was also significantly higher, (200.6) pg/ml versus (96.34) pg/ml in the control group. Conclusion: The mean tumor necrosis factor-α level was higher in patients with hyperemesis gravidarum than in women with normal pregnancy.